Realism Vs Idealism. Ross And Castberg. Paths Of A Dispute Upon Law And Human Rights - Serpe, Alessandro (Frónesis, 1970)
In Scandinavia, an animated debate arose in the 40”™s between the Swedish legal philosophers supporting H í¤gerstr í¶m”™s “theory of reality” and some Logic Empiricism”™s postulates and, in opposition, a moderate attempt to re-propose Natural Law and the normative concept of Law, represented by the Norwegian Frede Castberg. This study focuses on the theoretical differences between the Scandinavian Realism and the Idealism, mostly by highlighting Castberg”™s normative Idealism and his programme of ”˜modern”™ Natural Law. It follows a deepened analysis of Castberg”™s criticism toward Ross”™s ”˜realistic”™ approach concerning democracy, freedom, equality and human rights. By taking these two contrasting viewpoints into account, this study pays attention to the very colourful Norwegian theoretical debate on human rights by describing the contribution of some authors which, although theoretically inspired by Realism, Pragmatism and Analytical Philosophy, seem to reap the harvest of Idealism”™s efforts. The research main role is to clarify, through methodological comparison, the different traditions of Realism and Idealism as to the epistemological foundation of the concepts of Law and human rights. Moreover, this study, through an investigation of a large parts of literature, sheds light upon the implications of such theories within the field of the practice of human rights